Penguatan Kader Posyandu Desa Mlawang Klakah Lumajang Melalui Pengolahan PMT Halal dan Thayyib sebagai Tindakan Preventif Cegah Stunting - Badrotin Jabbar, Achmad Arbi Nur; Nurazizah, Devia Rahma; Pangestu, Fikri Ari; Laili, Izza Nuzilatul; Zahro, Fatimatus; Rahmawati, Lilik (Universitas Dinamika, 2025)
Stunting in Indonesia is a national health problem that is recorded as high. In order to minimize it, optimizing the role of posyandu cadres in processing halal and thayyib supplementary food (PMT) in Mlawang Village is the main focus of this community service activity. The method used in carrying out this community service is by using the Asset Based Community Development (ABCD) method, there are five steps, namely, discovery, dream, design, define, destiny. Therefore, this community service activity was carried out to improve the understanding and skills of posyandu cadres in processing halal and thayyib PMT as a preventive measure to prevent stunting. Based on the pre-test value of 50% which increased in the post-test to 95%, it can be concluded that the activities in the form of education and training have had a very good impact.